PENGARUH KINERJA KEPEMIMPINAN DAN MANAJEMAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SD NEGERI 1 BATU PUTUK KOTA BANDAR LAMPUNG - Meri Lusiyanti; Sri Rahayu Ningsih (UNISAN JURNAL, 2024)
This study aims to analyze the influence of the school principal's leadership performance and management on teacher performance at SD Negeri 1 Batu Putuk, Bandar Lampung City. Effective leadership and management practices are crucial for improving teacher performance and, consequently, student outcomes. This research employs a quantitative approach, utilizing surveys and performance evaluations to gather data. The results indicate that the principal's leadership performance significantly impacts teacher performance. Key factors include the principal's ability to communicate vision, provide support, and foster a positive school culture. Additionally, effective management practices, such as resource allocation, professional development, and organizational planning, contribute to enhancing teacher performance. Challenges identified in the study include limited resources, resistance to change among staff, and balancing administrative duties with instructional leadership. Efforts to overcome these challenges involve continuous professional development for the principal, fostering a collaborative environment, and involving teachers in decision-making processes. In conclusion, the leadership and management performance of the school principal play a vital role in shaping the performance of teachers at SD Negeri 1 Batu Putuk. Strengthening these aspects can lead to significant improvements in teaching quality and student achievement